(3GdefGgL GdJYdjejI GdLOjOI hOhQgG aj JfejI GdehGQO GdHTQjI aj GdeOQSI GdeJhSWI GdQSejI(B. (3fehPL eOQSI HjUhQ GdeJhSWI GdQSejIs - (3hgHg, HTQis ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2013)
(3JgOa gPg GdOQGSI Edi JMOjO eYGde GdefGgL GdJYdjejI GdMOjKI aj GdeOGQS GdQSejI hOQLI JWhQgG Yf GdefGgL GdbOjeI, hJMOjO GdXQha GdJj QGabJ JMOjKgG, HGdEVGaI Edi GdGWdGY Ydi OhQ GdefGgL aj JaYjd GdeTGQcI hJecjf GdWdGH ef GdYed GdLeGYj GdeTJQc, heYQaI OhQgG hJCKjQgG aj JfejI GdehGQO GdHTQjI hQaY GdcaGAI GdEfJGLjI(B. (3HGdJGdj GdJYQa Ydi GdUYhHGJ hGdKZQGJ GdJj JhGLg GdeYdejf NdGd YedjI JWHjb GdefGgL(B. (3EYJeO GdefgLGf GdhUaj GdJMdjdj hGdhUa GdGLJeGYj, hGbJUQJ GdOQGSI Ydi eOQSI HjUhQ GdeJhSWI GdQSejI, HMjK JeJ ebGQHI JWHjb GdefGgL ef NdGd GdPjf jbhehf HGdYedjI GdJYdjejI ef LgI hGdeJdbjf ef LgI CNQi(B. (3CLQjJ ebGHdGJ eY LejY eYdej GdeOQSI hYOOge (B43 (3eYdekG heYdeI, hhRYJ ESJeGQGJ Ydi (B55 (3WGdHkG ef GdUa GdJGSY CSGSj deYQaI GdUYhHGJ GdJj JhGLgge aj eNJda GdehGO, HGdEVGaI Edi GYJeGO JbfjI JMdjd GdeMJhi hGdeYdheGJ, hELQGA MhGQ eaJhM eY GdCSGJPI hGdEOGQjjf(B. (3HjfJ GdfJGFL Cf eYXe CaQGO GdgjFI GdJYdjejI aj GdeOGQS GdQSejI jUfahf aj GdaFI GdYeQjI GdeJbOeI Cj Ydi eTGQa GdJbGYO eeG bO jDOj Edi UYhHGJ aj JWHjb GdefGgL GdLOjOI(B. (3hdhMX JYjjf YThGFj ddeYdejf, hfSHI cHjQI ef CSGJPI GdedGc dG JeJdc TgGOGJ YdjG Ch ELGRGJ, eeG jDOj Edi UYhHI GSJjYGH GdefGgL GdLOjOI hGdbOQI Ydi JWHjbgG(B. (3ceG JHjf GQJaGY fSH fLGM Ua GdJGSY HYO JWHjb GdefGgL GdLOjOI, Cj Cf EOQGL GdefGgL GdJYdjejI GdLOjOI bO jDOj Edi EQJaGY fSHI fLGM GdWdGH aj GdGeJMGfGJ GdQSejI(B. (3ceG JHjf Cf GdYdGbI GdeJQGHWI Hjf GdCgd hGdeOQSI hGdWdGH bO JDOj Edi hUhd GdefGgL GdJYdjejI Edi JMbjb ZGjGJgG, acdeG cGf GdJaGYd bhjkG hefSLekG Hjf echfGJ hYfGUQ GdYedjI GdJYdjejI, cdeG cGfJ GdcaGAI GdEfJGLjI YGdjI Ydi eSJhi eNQLGJ GdJYdje(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Curricula; Curriculum; Human Resources; Public Sector Intermediate Education; Ressources Humaines; Secteur Public Cycle moyen; (3GdJYdje GdQSej GdeQMdI GdeJhSWIs; (3GdefGgLs; (3GdehGQO GdHTQjIs; (3HjUhQs